2016
DOI: 10.1371/journal.pntd.0004842
|View full text |Cite
|
Sign up to set email alerts
|

A Sequence of Flushing and Drying of Breeding Habitats of Aedes aegypti (L.) Prior to the Low Dengue Season in Singapore

Abstract: In dengue-endemic areas, transmission shows both a seasonal and interannual variability. To investigate how rainfall impacts dengue seasonality in Singapore, we carried out a longitudinal survey in the Geylang neighborhood from August 2014 to August 2015. The survey comprised of twice-weekly random inspections to outdoor breeding habitats and continuous monitoring for positive ones. In addition, observations of rainstorms were collected. Out of 6824 inspected habitats, 67 contained Aedes aegypti, 11 contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 39 publications
2
52
0
1
Order By: Relevance
“…Ehelepola et al [ 53 ] have found that regular rain favors an increase in dengue but not heavy rain. Similarly, Sarfraz [ 54 ] noted that heavy rainfalls may flush away the eggs, larvae and pupae of dengue mosquitoes, which could have consequently affected the mosquito abundance [ 55 ]. On the other hand, we have observed that moderate amount of rainfall (20–30 mm) was related to higher dengue incidences in Davao Region.…”
Section: Discussionmentioning
confidence: 99%
“…Ehelepola et al [ 53 ] have found that regular rain favors an increase in dengue but not heavy rain. Similarly, Sarfraz [ 54 ] noted that heavy rainfalls may flush away the eggs, larvae and pupae of dengue mosquitoes, which could have consequently affected the mosquito abundance [ 55 ]. On the other hand, we have observed that moderate amount of rainfall (20–30 mm) was related to higher dengue incidences in Davao Region.…”
Section: Discussionmentioning
confidence: 99%
“…This study explores the influence of the pattern of urban housing on dengue distribution at a neighborhood and country scales. In a previous survey in Geylang between August 2014 and August 2015, we found that Aedes aegypti breeds mainly in clogged drains close to the housing (Seidahmed & Eltahir, ). These outdoor breeding habitats are clustered in the low‐rise housing part of the Geylang.…”
Section: Introductionmentioning
confidence: 86%
“…We calculated pupal density per 1,000 population by dividing estimates of Aedes pupae found in a grid cell by the total human population in that grid. Further details on this entomological survey can be found in (Seidahmed & Eltahir, ).…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between rainfall and mosquito populations is multifaceted, contributing to habitat creation and larval mortality. 32 Evidence both supports and contradicts the role of rainfall in vector establishment, especially during disease outbreaks, 33–35 where complex precipitation patterns, surface water dynamics and a diversity of time lags affect the local vector population size. 36–38 Another disputed proxy of moisture availability affecting these species is relative humidity, which is thought only to affect behavioural or survival vector changes at the extremes.…”
Section: Introductionmentioning
confidence: 99%